Dual silencing of lipophagy and lipolysis in Rhodnius prolixus induces lipid droplet remodeling without TAG accumulation in the fat body - Samara Santos-Araujo; Katia C. Gondim; Isabela Ramos (PLoS ONE, 2025)
Autophagy and lipolysis are key metabolic pathways involved in lipid mobilization and energy homeostasis. In Rhodnius prolixus , a major vector of Chagas disease, previous studies have shown that silencing autophagy-related genes ( RpAtg8 , RpAtg6 ) or the brummer lipase gene RpBmm alters lipid metabolism and impairs flight activity. Here, we investigate the combined roles of lipolysis and lipophagy by performing a dual RNAi-mediated silencing of RpAtg8 and RpBmm under both fed and starved conditions. In the fat body, dual silencing did not exacerbate triacylglycerol (TAG) accumulation beyond single knockdowns but led to significant enlargement of lipid droplets (LDs), suggesting adaptive remodeling. In contrast, the flight muscle of fed insects showed additive increases in TAG content, indicating synergistic impairment of lipid mobilization under this condition. Dual knockdown also modulated expression of lipid metabolism-related genes, including AKHr , Dgat1/2 , and Plin1 , in a tissue- and condition-specific manner. Combined silencing reduced vitellogenin levels in the hemolymph, significantly compromised oviposition, hatching success, survival, as well as flight capacity. Nonetheless, none of the phenotypes observed in the dual-silenced group showed additive effects when compared to the single knockdowns. Thus, while some phenotypes appeared additive, particularly in TAG accumulation in the flight muscle (only under fed conditions) and fat body LD remodeling, most impairments were not changed by the dual knockdown. These results highlight the crucial but apparent redundant roles of lipolysis and autophagy in maintaining lipid homeostasis and ensuring reproductive success in R. prolixus .